Protective role of mitophagy on microglia-mediated neuroinflammatory injury through mtDNA-STING signaling in manganese-induced parkinsonism - Yang Lu; Liang Gao; Yuqing Yang; Dihang Shi; Zhipeng Zhang; Xiaobai Wang; Ying Huang; Jie Wu; Jia Meng; Hong Li; Dongying Yan (Journal of Neuroinflammation)
Abstract Manganese (Mn), the third most abundant transition metal in the earth’s crust, has widespread applications in the emerging field of organometallic catalysis and traditional industries. Excessive Mn exposure causes neurological syndrome resembling Parkinson’s disease (PD). The pathogenesis of PD is thought to involve microglia-mediated neuroinflammatory injury, with mitochondrial dysfunction playing a role in aberrant microglial activation. In the early stages of PD, PINK1/Parkin-mediated mitophagy contributes to the microglial inflammatory response via the cGAS/STING signaling pathway. Suppression of PINK1/Parkin-mediated mitophagy due to excessive Mn exposure exacerbates neuronal injury. Moreover, excessive Mn exposure leads to neuroinflammatory damage via the microglial cGAS-STING pathway. However, the precise role of microglial mitophagy in modulating neuroinflammation in Mn-induced parkinsonism and its underlying molecular mechanism remains unclear. Here, we observed that Mn-exposed mice exhibited neurobehavioral abnormalities and detrimental microglial activation, along with increased apoptosis of nerve cells, proinflammatory cytokines, and intracellular ROS. Furthermore, in vivo and in vitro experiments showed that excessive Mn exposure resulted in microglial mitochondrial dysfunction, manifested by increased mitochondrial ROS, decreased mitochondrial mass, and membrane potential. Additionally, with the escalating Mn dose, PINK1/Parkin-mediated mitophagy changed from activation to suppression. This was evidenced by decreased levels of LC3-II, PINK1, p-Parkin/Parkin, and increased levels of p62 protein expression level, as well as the colocalization between ATPB and LC3B due to excessive Mn exposure. Upregulation of mitophagy by urolithin A could mitigate Mn-induced mitochondrial dysfunction, as indicated by decreased mitochondrial ROS, increased mitochondrial mass, and membrane potential, along with improvements in neurobehavioral deficits and attenuated detrimental microglial activation. Using single-nucleus RNA-sequencing (snRNA-seq) analysis in the Mn-exposed mouse model, we identified the microglial cGAS-STING signaling pathway as a potential mechanism underlying Mn-induced neuroinflammation. This pathway is associated with an increase in cytosolic mtDNA levels, which activate STING signaling. These findings point to the induction of microglial mitophagy as a viable strategy to alleviate Mn-induced neuroinflammation through mtDNA-STING signaling. Graphical Abstract